Synthesis of chitin from exoskeleton of Shrimp and factors affecting adsorption of dye on Chitin (International Journal of Food and Nutritional Sciences, 2022)
The control of water pollution is becoming increasingly important these days. Release of dyes into the environment constitutes a small portion of water pollution. The adsorption process is one of the effective methods for removal of dyes from the waste effluent. Chitin has been utilized as an adsorbent for a variety of substrates. Chitin can be used as adsorbent in the treatment of effluents from the textile industry, especially for triphenyl methane. In present research, preparation of chitin was done from fishery waste. Study of the effect of pH and agitation time on adsorption of xylenol orange dye on chitin was also carried out. The maximum adsorption of xylenol orange dye was observed at 445 nm under the U.V Spectrophotometer. It was interesting to note that the pH range for maximum adsorption at different agitation times remains between 3 to 4 only. It was observed that maximum adsorption of dye occurs at 10 minutes agitation time and in a pH range of 3 to 4.